KOMIK PENGENALAN ANGKA UNTUK ANAK USIA DINI DI KOTA METRO - Isnaini Nur Azizah (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
This research aims to create educational product of comics. This product make media to introduce numbers for early childhood. The subjects in this study were students for early childhood. They are TK Ma'arif 1 at 16c Metro South, TK Ma'arif 2 at 21 East Metro and RA Ma'arif 1 at 28 Purwosari Metro Utara. The development model used is the 4D development model, Thiagarajan which consists of 4 stages, define, design, develop and disseminate. The results of the material expert validation with a score of 3.60 with a very valid category. The results of design validation with a score of 3.43 with a very valid category. The results of the field test as much as 86% reached the indicator that the child could show / pronounce the names of numbers verbally and in writing, as many as 77% of the children reached the indicator which was able to write and mention the names of the numbers in order and consistently, as many as 69% of the children reached the indicator that was able to understand correspondence (for example